The Development of the Screening Tool Toddlers & Young Children at Risk for Autism Spectrum Disorders - คุณชื่น พัชรีวรรณ (Ratchaphruek Journal, 2019)
The objective of this research was to develop the screening tool in toddlers and young children at risk for Autism Spectrum Disorders (ASD). The sample of this research were 520 toddlers and young children in Preschool Child Development Center in Bangkok. Teachers who supervised the children acted as the assessors. The research instrument was the screening scale in toddlers and young children at risk for Autism Spectrum Disorders (ASD). the questionnaire was sent to the experts for further verification and confirmation on its validity of criterion and content. 36 items of questions were concluded and trialed with teachers who supervised the children acted as the assessors in Preschool Child Development Center in Bangkok. Data collected were then analyzed to determine the reliability, validity, and Pearson’s correlation coefficient. The results of this research indicated that the validity of the developed screening scale in toddlers and young children at risk for Autism Spectrum Disorders (ASD) was between .80 and 1.00. This implied that the scale quality was acceptable and could be practically used for screening. The reliability ( ) of the screening scale for both overall and individual aspects, including social communication and social interaction and behavior and interest were at a very good level ( = .91, .84, and .87, respectively). For the correlation coefficients between Modified Checklist for Autism in Toddlers (M-CHAT) and the reliability ( ) of the developed screening scale was .97. This implied that the developed screening scale had very high correlation and could be practically applied to screen toddlers and young children at risk for Autism Spectrum Disorders (ASD).